Assessing systemic risks and predicting systemic events - Duca, Marco Lo; Peltonen, Tuomas A. (Journal of Banking & Finance, 2013)
The paper develops a framework for assessing systemic risks and for predicting systemic events, i.e. periods of extreme financial instability with potential real costs. It contributes to the literature on the prediction of financial crises mainly in two ways: first, it uses a Financial Stress Index for identifying the starting date of systemic financial crises. Second, it uses discrete choice models that combine both domestic and global indicators of macro-financial vulnerabilities to predict systemic financial crises. The performance of the models is evaluated in a framework that takes into account policy maker’s preferences between missing crises and issuing false alarms. Our analysis shows that combining indicators of domestic and global macro-financial vulnerabilities substantially improves the models’ ability to forecast systemic financial crises. Our framework also displays a good out-of-sample performance in predicting the ongoing Global Financial Crisis.